Numerical Analysis of Influence of Thickness of Liquid Film on Bottom Cover to Heat Transfer in Thermosyphon in Conditions Emergency Modes of Work the Rechargeable Batteries of Aircrafts - Krasnoshlykov A. S. Aleksandr Sergeevich (2016, 2016)
Title screen